THE DEVELOPMENT OF HANDOUT BASED ON GUIDED NOTE TAKING TO IMPROVE THE QUALITY OF ANALYTICAL CHEMISTRY LEARNING - Sari, Sri Adelila; Jasmidi, .; Kembaren, Agus; Sudrajat, Ajat (PEOPLE: International Journal of Social Sciences, 2018)
Learning quality of a student is also influenced by the availability of teaching materials which can be in the form of handouts as print materials that are very economical and practical. The long-term goal of this research was to improve the quality of analytical chemistry learning in the Chemistry Department, Medan State University, Indonesia. While the specific target was to develop innovative teaching materials, called Handout based on Guided Note Taking (HGNT). The method used was Research & Development followed 4 stages: define, design, develop and disseminate (4-D). The defining approach aimed to define the need for developing handouts and this stage found that students were very difficult to understand analytical chemistry which related to chemical separation. The second stage was to design HGNT. The cover and content were designed as attractive as possible. The title, time allocation, and learning objectives were adapted to the syllabus. Tables and images used appropriate forms and attractive color combinations. Then all interrelated data were used for the third stage, which was developed. Contents development consisted of the separation concepts, distillation, sublimation, and extraction, and bleaching. Furthermore, it was validated by two experts with some aspects, i.e., presentation, visualization, and media clarity. The average of validation value was reached of 85 percent, which means very feasible to use. Furthermore, in the fourth stage, the dissemination was carried out to 3rd year of 35 students in an odd semester. Students and lecturer responses were measured using questionnaire and the positive responses were found to be 80.30 and 95 percent, respectively with excellent criteria. Student learning outcomes showed an increase from 70.81 to 97.00 for the subtopics with five meetings. This study concluded that HGNT could improve the learning quality of students in analytical chemistry learning.